Split-face comparison of the combined Er-YAG laser and hydroquinone 4% with hydroquinone 4% alone in the treatment of melasma in Iranian patients: Prospective, interventional case study - Namazi, Nastaran; Ketabi, Yasaman; Hesami, Aida (Journal of Lasers in Medical Sciences, 2020)
Introduction: Melasma is one of the most common skin pigmentation disorders, which mostly affects the facial skin and has a considerable psychological impact on the patients. Melasma management has been one of the controversial issues in dermatology. We aimed to compare the combined treatment of the Er: YAG (erbium: yttrium–aluminum–garnet) laser plus hydroquinone (HQ) 4% with HQ 4% alone in the treatment of melasma. Methods: Twenty-nine patients were treated with the combined Er: YAG laser and HQ 4% on one side of the face with HQ 4% alone on the other side. Three sessions of the laser rat 4-week intervals. The outcome was calculated using the Melasma Area Severity Index (MASI). Results: The side that received the combined treatment (laser + HQ 4%) showed a statistically significant reduction in MASI compared to the side treated with HQ 4% alone. Conclusion: Our study suggests the superiority of the combination of the Er: YAG laser and HQ 4% in the treatment of melasma compared to HQ 4% alone.